2020
DOI: 10.1371/journal.pone.0238857
|View full text |Cite
|
Sign up to set email alerts
|

Propofol induces mitochondrial-associated protein LRPPRC and protects mitochondria against hypoxia in cardiac cells

Abstract: Background Hypoxia-induced oxidative stress is one of the main mechanisms of myocardial injury, which frequently results in cardiomyocyte death and precipitates life-threatening heart failure. Propofol (2,6-diisopropylphenol), which is used to sedate patients during surgery, was shown to strongly affect the regulation of physiological processes, including hypoxia-induced oxidative stress. However, the exact mechanism is still unclear. Methods Expression of LRPPRC, SLIRP, and Bcl-2 after propofol treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Although Fis1 was also reported to play a role in mitochondrial fission [ 33 ], we found it was not affected by hypoxia ( Figure 5(a) ). In addition, we reported in hippocampal neurons hypoxia-induced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1 α ( Figure 6(a) ), which was consistent with previous publications carried out in fibroblasts [ 30 ], cardiac cells [ 22 ], and vascular smooth muscle cells [ 34 ]. Although other transcription factors such as Smad2/3 [ 35 ], NF- κ B [ 36 ], and calcium-related transcription factors [ 37 ] have been reported to correlate with Drp1 expression, we demonstrated that HIF-1 α inhibitors could almost completely inhibit hypoxia-induced Drp1 expression ( Figure 6(b) ), and thus, suggesting the pivotal role of HIF-1 α .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although Fis1 was also reported to play a role in mitochondrial fission [ 33 ], we found it was not affected by hypoxia ( Figure 5(a) ). In addition, we reported in hippocampal neurons hypoxia-induced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1 α ( Figure 6(a) ), which was consistent with previous publications carried out in fibroblasts [ 30 ], cardiac cells [ 22 ], and vascular smooth muscle cells [ 34 ]. Although other transcription factors such as Smad2/3 [ 35 ], NF- κ B [ 36 ], and calcium-related transcription factors [ 37 ] have been reported to correlate with Drp1 expression, we demonstrated that HIF-1 α inhibitors could almost completely inhibit hypoxia-induced Drp1 expression ( Figure 6(b) ), and thus, suggesting the pivotal role of HIF-1 α .…”
Section: Discussionsupporting
confidence: 92%
“…also reported to play a role in mitochondrial fission [33], we found it was not affected by hypoxia (Figure 5(a)). In addition, we reported in hippocampal neurons hypoxiainduced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1α (Figure 6(a)), which was consistent with previous publications carried out in fibroblasts [30], cardiac cells [22], and vascular smooth muscle cells [34].…”
supporting
confidence: 92%
See 2 more Smart Citations
“… 31 , 32 , 33 In addition, LRPPRC could regulate mitochondrial homeostasis through targeting HIF1-α. 34 Therefore, LRPPRC might regulate the ROS/HIF1-α pathway through affecting autophagy and further influence mitochondrion function. Knockdown of LRPPRC slightly upregulated the expression of ROS/HIF1-α, but treatment with the lysosomal inhibitor suppressed the level of ROS/HIF1-α, indicating LRPPRC could activate the ROS/HIF1-α pathway via suppressing autophagy.…”
Section: Discussionmentioning
confidence: 99%